2010
DOI: 10.1161/hypertensionaha.110.156786
|View full text |Cite
|
Sign up to set email alerts
|

Methylglyoxal Is a Predictor in Type 2 Diabetic Patients of Intima-Media Thickening and Elevation of Blood Pressure

Abstract: Abstract-We test whether plasma level of methylglyoxal (MG) is an independent risk factor predicting the progression of diabetic macroangiopathy or microangiopathy in type 2 diabetic patients. We measured in 50 type 2 diabetic patients plasma levels of MG and 3-deoxyglucosone (DG) using an electrospray ionization-liquid chromatography-mass spectrometry. We assessed the correlations between baseline levels of MG or DG and the percentage changes after 5 years of clinical parameters linked to diabetic macroangiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
69
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 29 publications
5
69
0
Order By: Relevance
“…MGO is known to have detrimental effects on cellular function and it is also evident that elevated levels of MGO are responsible for renal oxidative stress, as demonstrated in diabetic rats [10]. Most importantly, progression of hypertension and diabetic nephropathy in humans is also significantly related to increased levels of MGO [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…MGO is known to have detrimental effects on cellular function and it is also evident that elevated levels of MGO are responsible for renal oxidative stress, as demonstrated in diabetic rats [10]. Most importantly, progression of hypertension and diabetic nephropathy in humans is also significantly related to increased levels of MGO [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…A recent report demonstrated that elevation of blood pressure (BP) of type 2 diabetic patients was associated with increase of plasma MGO level (9). Moreover, a previous report demonstrated that MGO accumulated in aorta of spontaneously hypertensive rats (SHR) with aging and that the increased MGO accumulation correlated with increase of BP (10).…”
Section: Introductionmentioning
confidence: 99%
“…Blood angiopoietin-2 levels rise in line with the decline in renal function and they serve as a predictor of CVREs. [28][29][30][31][32] Thus, it appears likely that impaired intrarenal blood flow due to arteriosclerosis, as well as renal damage due to renal ischemia caused by sclerotic changes in peripheral vessels (ie, arterioles) rather than by RAAS itself, and the increased angiopoietin-2 levels triggered under these circumstances, might intervene in a complicated manner to cause further cardiovascular/renal disorders. Accordingly, a decline in renal function and elevated angiopoietin-2, as opposed to stenotic lesion itself, might be associated with the heightened incidence of CVREs in type 2 diabetic patients with RAAS (Supplementary File 1-8).…”
Section: Discussionmentioning
confidence: 99%